EXTH-42. QUANTITATIVE BIODISTRIBUTION OF ADOPTIVELY TRANSFERRED T CELLS IN BRAIN TUMOR-BEARING MICE. (11th November 2019) - Hoang-Minh, Lan; Pohl-Guimarães, Fernanda; Rivera-Rodriguez, Angelie; Currlin, Seth; Otto, Kevin; Rinaldi, Carlos; Mitchell, Duane
Abstract: SIGNIFICANCE: Adoptive T cell therapy (ACT) has emerged as the most effective treatment strategy against advanced malignant melanoma, eliciting remarkable objective clinical responses in up to 75% of patients with refractory metastatic disease, including those with lesions within the central nervous system. Importantly, immunologic surrogate endpoints that correlate with treatment outcome have been identified in these patients, with clinical responses being dependent on the migration of transferred T cells to sites of tumor growth. OBJECTIVE: We investigated the biodistribution of exogenously administered T cells in a murine model of glioblastoma at whole body, organ, and cellular levels. METHODS: T cells were isolated from the spleens of DsRed transgenic C57BL/6 mice and injected intravenously, after in vitro expansion and activation, in murine KR158B glioma-bearing mice. To determine transferred T cell spatial distribution, brains, lymph nodes, hearts, lungs, spleens, livers, kidneys and stomachs were isolated for active clearing, immunostaining, and 3D imaging using light sheet microscopy, or processed for fluorescent immunohistochemistry and confocal imaging. Transferred T cell quantification in various organs was performed using flow cytometry, 2D optical imaging (IVIS), and magnetic particle imaging (MPI) after ferucarbotran nanoparticle labeling. T cell distribution was also assessed in vivo using IVIS and MPI. RESULTS: The spleen, liver, and lungs accounted for more than 90% of transferred T cells in the body. The proportion of DsRed T cells in tumor-bearing brains was found to be very low, hovering below 1% (and representing ~15% of total tumor-infiltrating lymphocytes). Transferred T cells mostly concentrated at the periphery of the tumor mass and in proximity to blood vessels. CONCLUSIONS: The success of ACT immunotherapy for brain tumors likely requires optimization of delivery route, dosing regimen, and modification of tumor-specific lymphocyte trafficking and effector functions in order to achieve maximal penetration and persistence at sites of invasive tumor growth.